(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Information technology companies have a variety of strategic alternatives available to them.That Indian IT companies might have done considerably better if they had strategically utilized theiradvantages, notably in the branded software industry and the under-penetrated markets, is emphasized inthe article. Indian software businesses are increasingly investing considerably in training and cutting-edgeprogramming abilities in order to preserve their competitive advantage. A research of the IT-ITESindustry’s requirements on a national and worldwide scale was conducted in order to gain acomprehensive picture and evaluate the potential that exists in the IT sector. For India to staycompetitive in the global economy, the present business climate and emphasis areas make it evidentthat considerable efforts are needed.